The Court of Comedy : Aristophanes, Rhetoric, and Democracy in Fifth-Century Athens - Major, Wilfred E., 1967- (Book collections on Project MUSE., 2013)
In this book, the author analyzes how writers of comedy in Classical Greece satirized the emerging art of rhetoric and its role in political life. In the fifth century BCE, the development of rhetoric proceeded hand in hand with the growth of democracy both on Sicily and at Athens. In turn, comic playwrights in Athens, most notably Aristophanes, lampooned oratory as part of their commentary on the successes and failures of the young democracy. This study surveys all the surviving comedy from the fifth century BCE on these important topics. The evidence reveals that Greek comedy provides a revealing commentary on the incipient craft of rhetoric before its formal conventions were stabilized. Furthermore, Aristophanes' depiction of rhetoric and of Athenian democratic institutions indicates that he fundamentally supports the Athenian democracy and not, as is often argued, oligarchic opposition to it. These conclusions confirm recent work that reinterprets the early development of rhetoric in Classical Greece and offer fresh perspectives on the debate over the role of comedy in early Greek democracy. Throughout, the author capitalizes on progress in the understanding of the performance dynamics of Classical Greek theater.